PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAH, PEMANFAATAN TEKNOLOGI INFORMASI, KOMPETENSI SUMBER DAYA MANUSIA, PENERAPAN SISTEM PENGENDALIAN INTERN PEMERINTAH, DAN SISTEM AKUNTANSI KEUANGAN DAERAH TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH - Rama Ardianto; Chermian Eforis (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2019)
The purpose of this research was to examine the effect of several factors toward quality of local government’s financial statement. The factors consist of governmental accounting standards, utilization of information technology, competencies of human resource, government’s internal control system, and local financial accounting system. The samples of this research were the employees at Satuan Kerja Perangkat Daerah (SKPD) or regional work unit in Tangerang regency with several characteristic. The characteristics are, 1) using SIMDA as a financial accounting system and 2) involved during preparation of financial statements. The data used was primary data. This research used questionnaire for collecting data. The sampling technique is non-probability samping which is convenience sampling. The results of this research are: (1) governmental accounting standards has significant effect toward the quality of local government’s financial statement, (2) utilization of information technology has significant effect toward the quality of local government’s financial statement, (3) competencies of human resource has significant effect toward the quality of local government’s financial statement, (4) government’s internal control system does not affect toward the quality of local government’s financial statement, (5) local financial accounting system does not affect toward the quality of local government’s financial statement.